Epidemiological panorama of type 2 diabetes in Mexico: differences by state and social determinants - Guadalupe Soto-Estrada; Laura Moreno-Altamirano; Naghielli Álvarez-Chombo; Juan J. García-García (Revista Médica del Hospital General de México)
Introduction: Type 2 diabetes mellitus (T2DM) is a public health problem with an impact on individuals and society. Objective: The study aimed to describe the rates of variation and the rate of growth of the prevalence and mortality of T2DM in the states of Mexico, in relation to the figures of multidimensional poverty and indicators of social deprivation, the Human Development Index, the Gini Coefficient and GDP per capita. Material and methods: An ecological study was carried out with information from official open access sources in Mexico, the prevalence and mortality of T2DM were analyzed. The entities were grouped according to their rates of change, and their growth rates were analyzed according to the socio-economic context. A correlation analysis was performed between the rate of variation of mortality and the prevalence of T2DM with the percentage of the population living in extreme poverty. Results: Both indicators have increased in all entities at different rates. The poorest states, with the lowest Human Development Index and GDP and the highest Gini coefficient have been the most affected. The correlation showed that, the higher the level of extreme poverty, the higher the increase in mortality and the prevalence of T2DM. Conclusion: If the care strategy is not modified, this accelerated increase will mainly affect the poorest entities, which, due to their access to health services and living conditions, will have more far-reaching consequences.